Hubungan Antara Self Efficacy Dengan Prokrastinasi Akademik Siswa - Wahid Nurshodiq; Umbu Tagela; Yustinus Windrawanto (Journal Prakarsa Paedagogia, 2023)
This study aims to determine the significance of the relationship between Self-Efficacy and Academic Procrastination in Class XII Students of SMK Nusa Persada, Semarang Regency. This type of research is a correlational study that aims to determine whether there is a relationship or not there is a relationship between two or more variables. The population in this study was 41 students of Class XII at Nusa Persada Vocational School, Semarang Regency. The sampling technique in this study is total sampling. Data of this research were analyzed by using Kendall's Tau-b correlation analysis. based on the results of data analysis, the correlation coefficient value was -0.463 with a significance value of 0.001. These results indicate that there is a negative and significant relationship between self-efficacy and academic procrastination in class XII students at Nusa Persada Vocational School, Semarang Regency.